MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK MELALUI MEDIA KARTU ANGKA PADA ANAK USIA 5-6 TAHUN DI TK KRISTEN REHOBOTH - Maria M. Anselwain; Hermelina Abarua; Lambertus J. Lokollo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research addresses the issue of suboptimal cognitive development in children aged 5-6 years at Rehoboth Christian Kindergarten in Ambon, where many children struggled to count from 1 to 10 and match numbers with their symbols. The study aimed to determine how number card media could improve children's cognitive development. Using classroom action research methodology, the study was conducted over two cycles with 16 children (11 boys and 5 girls). Each cycle consisted of planning, implementation, observation, and reflection phases. Data collection involved observation, interviews, documentation, and tests to assess children's ability to recognize number symbols and match numbers with their symbols. Results showed significant improvement in cognitive development through the use of number cards. In the pre-cycle, most children were at the beginning development stage. By cycle I, 25% achieved excellent development (BSB), 12.5% met expectations (BSH), and 62.5% were developing (MB). By cycle II, these figures improved dramatically to 87.5% BSB, 12.5% BSH, with no children remaining in the MB or BB categories. This demonstrates that number card media effectively enhances cognitive development in early childhood education by making learning more engaging and concrete, helping children better understand number concepts and develop counting skills.